Balloon-occluded retrograde transvenous obliteration using a new microballoon for gastric varices. Issue 3 (4th May 2017) - Mine, Takahiko; Matsumoto, Tomohiro; Endo, Jun; Hashida, Kazunobu; Kojima, Seiichiro; Watanabe, Norihito; Hasebe, Terumitsu
Abstract: We here present a case involving a complicated type of gastric fundal varices treated by balloon-occluded retrograde transvenous obliteration. A newly developed 1.8-Fr tip coaxial microballoon catheter was successfully advanced into narrow and tortuous varices, and a sclerosant could be infused in a reasonable manner, avoiding reflux into collaterals. Divided injections of sclerosant were performed over two days, via a microballoon catheter that remained inserted overnight with balloon inflation, and the sclerosant could be infused sufficiently in the entirety of the varices. The varices were completely thrombosed and prominently reduced.